EVOLUTION OF DIGITAL MARKETING: FROM SEO TO AI-BASED PERSONALISATION - Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The evolution of digital marketing has shown a transformation from traditional techniques such as SEO (Search Engine Optimisation) to modern strategies supported by artificial intelligence (AI) and personalisation. Initially, digital marketing focused on increasing visibility on the internet through the use of keywords, backlinks, and optimal site structure. However, technological developments have brought about a shift towards a more in-depth data-driven approach, enabling a more accurate understanding of user behaviour and consumer preferences. Today, the integration of AI in digital marketing enables personalisation of content for users, with the ability to process big data and identify complex patterns. This technology not only improves efficiency but also provides a more relevant and human user experience. Thus, the future of digital marketing will continue to evolve as innovative technologies are adopted to meet increasingly complex consumer needs.